The Relative Contribution of the Flexibility for the Hip Joint, the Angle of the Knees, and the Muscular Strength for Arms of Performance of the Front and Back Rolling Skills, Opening on the Floor Movement Mat - Ibtihal Riyadh Omran; Intisar Kadhum Abdulkareem (Indian Journal of Forensic Medicine & Toxicology, 2021)
In order to improve the students’ performance level in some of the skills that are implemented on the mat device of ground movements, including the front and rear rolling, it is necessary to study the most important indicators that have a clear impact on the performance of those rolls. Among the objectives of the research: To identify the percentage of the contribution of flexibility of the hip joint, the angle of the knees and the muscular strength of the arms in the performance of the front and rear rolling skills, an opening of the research sample. The researchers used the descriptive method in the survey method for its suitability to the nature of the work, and the research community was represented by students of the third stage of the Department of Physical Education and Sports Sciences at the College of Education for Girls / University of Kufa, and their number reached (26) students, and the research sample was chosen by the random method by drawing a lot from the original community and their number ( 20) a student, and with this, the percentage of the research sample is (76.9%).